Analisis Pengaruh Ekspor, Nilai Tukar, dan Inflasi Terhadap Pertumbuhan Ekonomi di Indonesia Tahun 1993-2023 - Rissa Aruni Nabillah; Rosewita Akhmellia Putri; Antariksa Dara Nirmala; Yustirania Septiani (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
The focus of this research is how exports, exchange rates, and inflation affect Indonesia's economic growth. For 30 secondary data, the Ordinary Least Square (OLS) model is used. The results showed that there was an insignificant positive relationship between exports and economic growth, and that increased export activity could have an insignificant positive effect on economic growth. In addition, the depreciation of the rupiah exchange rate increases the competitiveness of domestic products in the international market, so that the rupiah exchange rate against foreign currencies also has a significant impact on economic growth. However, the results of the study show that inflation also has a negative impact on economic growth. The economy can be disrupted by declining people's purchasing power, stunted investment, and high inflation.